The Politics of U.S. International Trade: Protection, Expansion and Escapeby LenwayStephanie Ann. Boston: Pitman, 1985, 228 pp., $25.95, cloth. - Lenn, D. Jeffrey (Academy of Management Review, 1988)
The article presents a review of the book ?The Politics of U.S. International Trade: Protection, Expansion and Escape,? by Stephanie Ann Lenway.